Biologic Augmentation Reduces the Failure Rate of Meniscal Repair: A Systematic Review and Meta-analysis. Issue 2 (24th February 2021) - Zaffagnini, Stefano; Poggi, Alberto; Reale, Davide; Andriolo, Luca; Flanigan, David C.; Filardo, Giuseppe
Background: Clinical results after isolated meniscal repair are not always satisfactory, with an overall failure rate of around 25%. To improve the success rate of meniscal repair, different biologic augmentation techniques have been introduced in clinical practice, but their real efficacy is still controversial. Purpose/Hypothesis: To evaluate the safety, clinical results, and failure rate of biologic augmentation techniques for meniscal repair. The hypothesis was that biologic augmentation would improve the results of meniscal repair. Study Design: Systematic review and meta-analysis of comparative studies. Methods: A systematic review of the literature was performed in March 2020 of 3 electronic databases (PubMed, Scopus, and the Cochrane Library) regarding meniscal repair combined with biologic augmentation techniques. Articles combining biologic augmentation with other surgical procedures besides meniscal suture were excluded. The quality of the included studies was assessed using a modified Coleman Methodology Score, and the risk of bias was evaluated using the ROBINS-I (Risk of Bias in Non-randomized Studies of Interventions) and the RoB 2.0 (Revised Tool for Risk of Bias in Randomized Trials) for nonrandomized and randomized controlled trials, respectively. Results: A total of 11 studies were included in the qualitative analysis: platelet-rich plasma (PRP) augmentation in 6 comparatives studies, fibrin clot augmentation in 2 case series, and mesenchymal stem cells augmentation in 2 case series and 1 case report. One severe adverse event of septic arthritis was reported for PRP 1 month after surgery. The quality of evidence evaluated with the modified Coleman Methodology Score was low overall. Five studies reporting on 286 patients (111 PRP augmentation, 175 control) were included in the quantitative synthesis. A significantly lower risk of failure was documented in the PRP augmentation group as compared with the control group: 9.9% (4.5%-19.1%) versus 25.7% (12.7%-38.7%) ( P < .0005). Conclusion: The literature on biologic meniscal augmentation is recent and scarce. Only a few comparative trials are available, all focusing on the potential of PRP. The meta-analysis documented that PRP is safe and useful in improving the survival rate, with a 9.9% rate of failure versus 25.7% for the control group. Further high-level studies are needed to confirm these findings and identify the most effective biologic augmentation strategy to improve the outcome of meniscal repair.